Effect of temperature on the permeability of gas adsorbed coal under triaxial stress conditions. (9th February 2018) - Li, Xiangchen; Yan, Xiaopeng; Kang, Yili
Abstract: The combined effects of gas sorption, stress and temperature play a significant role in the changing behavior of gas permeability in coal seams. The effect of temperature on nitrogen and methane permeability of naturally fractured coal is investigated. Coal permeability, P-wave velocity and axial strain were simultaneously measured under two effective stresses and six different temperatures. The results showed that the behavior of nitrogen and methane permeability presented nonmonotonic changes with increasing temperature. The variation in the P-wave velocity and axial strain showed a good correspondence with coal permeability. A higher effective stress limited the bigger deformation and caused the small change in permeability. Methane adsorption and desorption significantly influence the mechanical properties of coal and play an important role in the variations in coal permeability. The result of coal permeability during a complete stress–strain process showed that the variation in permeability is determined by the evolution of the internal structure. The increase in the temperature of the gas saturated coal causes the complex interaction between matrix swelling, matrix shrinkage and micro-fracture generation, which leads to the complex changes in coal structure and permeability. These results are helpful to understand the gas transport mechanism for exploiting coal methane by heat injection.